Sociodemographic Determinants of Delivery Practices among Women in Bangladesh: A Community-based Study (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Maternal mortality remains a public health concern globally, particularly in low- and middle-income countries. Bangladesh has made significant progress in reducing maternal mortality and increasing institutional deliveries, but disparities and rising caesarean section (CS) rates persist.Objective: This study aims to explore factors influencing delivery practices among married women in Keraniganj Upazila, Dhaka, Bangladesh.Methods:This community-based cross-sectional study was conducted in March 2023 among 180 married women in Keraniganj Upazila near Dhaka, who had given birth within the last 10 years. Data were collected through face-to-face structured interviews using a semi-structured questionnaire covering socio-demographic characteristics, antenatal care (ANC), and delivery practices. Ethical approval was obtained from the Institute of Epidemiology, Disease Control and Research (IEDCR).Results: Most respondents (66.8%) were aged 20–30, and 91.7% had formal education. Half had migrant husbands. ANC attendance was high (95%), with 56.67% preferring private hospitals. Institutional deliveries accounted for 95% of births, with CS rates at 86.67%. Postnatal complications were reported in 6.67% of mothers and 1.67% of infants.Conclusion: The findings indicate a marked preference for private facility births alongside an alarming rate of cesarean deliveries, highlighting the urgent need for policy interventions.J Com Med Col Teachers’ Asso July 2025; 29(2):103-107